The Tiger in Rajasthan-a Study of its Habitat, Distribution and Status - Sankhala, K. S. (Indian Forester, 1969)
Rajasthan forms the extreme western limit of the present distribution of tigers in India. It is also a habitat of extreme heat, minimum humidity, insufficient cover and scarce water-holes. Past distribution shows that the animal had adapted very well even to this hostile habitat of adverse climate and cover, much different from his original home. The only favourite factor which held the tiger to such a climatic climax stage was adequate protection which provided plenty of natural game to prey on. In recent years biotic interference by man and his animals has reduced the tiger's domain by 50% and population to only 90 in the State.